2013
DOI: 10.1111/caim.12037
|View full text |Cite
|
Sign up to set email alerts
|

User‐Centric Service Map for Identifying New Service Opportunities from Potential Needs: A Case of App Store Applications

Abstract: Today, service innovation is just as important as product innovation. The ideation of service innovation, vis-à-vis product innovation, is user-oriented, rather than maker-oriented. Thus, capturing and understanding user context is key to being able to offer personalized and relevant services, and further identify new service opportunities. Therefore, a user-centric approach is needed in new service development, especially in the era of ubiquitous service. There exists a rich literature on how to incorporate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…More recent attempts at big data analysis for technology planning have included the introduction of other available technology planning data. These databases include trademarks, where product information extracted from trademarks is analyzed and linked to patent information as a means for identifying new technology opportunities [26], online customer complaints, where customer requirements are identified and considered as part of a new product development [27], mobile service applications, where online user behavior patterns are observed in order to suggest new business opportunities [28][29][30], and other data collected from various channels (e.g., wireless sensor networks) to be used for business operations and risk management [31].…”
Section: Big Data Analysis In Technology Planningmentioning
confidence: 99%
“…More recent attempts at big data analysis for technology planning have included the introduction of other available technology planning data. These databases include trademarks, where product information extracted from trademarks is analyzed and linked to patent information as a means for identifying new technology opportunities [26], online customer complaints, where customer requirements are identified and considered as part of a new product development [27], mobile service applications, where online user behavior patterns are observed in order to suggest new business opportunities [28][29][30], and other data collected from various channels (e.g., wireless sensor networks) to be used for business operations and risk management [31].…”
Section: Big Data Analysis In Technology Planningmentioning
confidence: 99%
“…Since smart services are generated and consumed by customers on a daily basis (Allmendinger and Lombreglia 2005;Wang et al 2006;Kim et al 2013), the manner of using and consuming these services should be reflected. This is realized by adopting the concept of ''user context.''…”
Section: Construction Of Service Dimensionsmentioning
confidence: 99%
“…Dey (2001) developed four categories of user context: identity, location, status (or activity), and time. Kim et al (2013) suggested the concept of location, event, objective (LEO) to construct a dictionary of potential user needs.…”
Section: Construction Of Service Dimensionsmentioning
confidence: 99%
“…The approaches of (1) [18], [19], [20], [21] are situated in a wide range of scientific fields. The highest relation to the described context could be found in [18].…”
Section: B Service Map Conceptmentioning
confidence: 99%
“…The catalogrelated objective of service retrieval and the construction system-related objective of creating atomic and composite services are not addressed. In [19] the authors categorize mobile services and apps with the help of a scale involving dimensions of 'customer needs'. The revelation of 'empty spaces' within the maps helps identifying yet not satisfied combinations of different customer needs that could be covered by innovative new services or apps.…”
Section: B Service Map Conceptmentioning
confidence: 99%